Handbook of Marine Macroalgae 2011
DOI: 10.1002/9781119977087.ch1
|View full text |Cite
|
Sign up to set email alerts
|

Biological Importance of Marine Algae

Abstract: Marine organisms are potentially prolific sources of highly bioactive secondary metabolites that might represent useful leads in the development of new pharmaceutical agents. Algae can be classified into two main groups; first one is the microalgae, which includes blue green algae, dinoflagellates, bacillariophyta (diatoms).. . etc., and second one is macroalgae (seaweeds) which includes green, brown and red algae. The microalgae phyla have been recognized to provide chemical and pharmacological novelty and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 207 publications
2
72
0
7
Order By: Relevance
“…Red seaweeds are considered the most important source of many biologically active me tabolites in comparison to other algal classes (El Gamal, 2010). As a first step toward identifying the major chemical groups present in D. obtusata, we have developed a qualitative chemical study of its composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Red seaweeds are considered the most important source of many biologically active me tabolites in comparison to other algal classes (El Gamal, 2010). As a first step toward identifying the major chemical groups present in D. obtusata, we have developed a qualitative chemical study of its composition.…”
Section: Discussionmentioning
confidence: 99%
“…A group of inhibitors of phospholipase A 2 were isolated from different microalgae (Mayer et al, 1993). Recently, other metabolites with antiinflammatory activity have been obtained from seaweeds, including a glycosterol (Awad, 2000), a phlorotannin (Sugiura et al, 2006), polyphenols (Jung et al, 2009;El Gamal, 2010) and polysaccharides (Ananthi et al, 2010). Moreover, various seaweeds have antinociceptive properties (Anca et al, 1993;Guzmán et al, 2001;Viana et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Marine organisms are sources of bioactive secondary metabolites with potent use in the development of new pharmaceutical agents (Abedin &Taha, 2008;Abdel-Raouf et al, 2008 andEL-Gamal, 2010). Kuniyoshi et al (1985) reported that, diphenyl ether extracted from the green alga Cladophora fascicularis was found to inhibit the growth of Escherichia coli, Bacillus subtilis and Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%
“…Marine macroalgae are a rich source of various phenolic antioxidant compounds [35][36][37][38][39]. These compounds exhibit a wide range of physiological properties, such as anti-allergenic, anti-artherogenic, anti-inflammatory, anti-microbial, anti-thrombotic, cardioprotective, vasodilatory, and antioxidant effects [1,36,37,40,41]. Structurally, phenolic compounds comprise an aromatic ring, bearing one or more hydroxyl substituents, and range from simple phenolic molecules to highly polymerized compounds [42].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Recent studies have demonstrated that the protective effect against oxidative stress induced by ROS and UV radiation is connected to the number and position of hydrogen-donating hydroxyl groups on the aromatic ring of the phenolic molecules, and is also affected by the other factors, such as other H-donating groups (-NH, -SH). Therefore, since dieckol has more hydroxyl groups than other phlorotannins it should be effective as an anti-oxidant for use in cosmeceutical products [1,40,49].…”
Section: Phenolic Compoundsmentioning
confidence: 99%